Nilai-Nilai Kearifan Lokal “Sesenggak” Serta Relevansinya Dengan Pendidikan Berkarakter - H, Hilmiyatun (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of the study is to describe the values contained in the local wisdom of "sesenggak" both in terms of form, meaning and function of sesenggak, and its relevance to character education. Thus, through this "sesenggak" we can instill good values in character education based on local wisdom. The methods used to achieve these goals include data collection methods and data analysis methods. The data collection methods used are the participant observation method, interview method, and documentation method. The observation method is used as an initial mapping to determine the problem. In the data collection stage, the observation technique used is participant observation with the aim of obtaining a real picture so that the validity of the data can be accounted for. Meanwhile, the documentation data analysis method is used to obtain data that supports primary data. Data analysis is carried out by data collection, data reduction, data presentation, and verification. The results of the discussion contain several sesenggak values that are relevant to character education, including social care character education, honest character education, democratic character education, communication/friendship character education, and hard work character education.